2022
DOI: 10.4266/acc.2021.01354
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm ultrasound as a better predictor of successful extubation from mechanical ventilation than rapid shallow breathing index

Abstract: Background: In 3%-19% of patients, reintubation is needed 48-72 hours following extubation, which increases intensive care unit (ICU) morbidity, mortality, and expenses. Extubation failure is frequently caused by diaphragm dysfunction. Ultrasonography can be used to determine the mobility and thickness of the diaphragm. This study looked at the role of diaphragm excursion (DE) and thickening fraction in predicting successful extubation from mechanical ventilation. Methods: Thirty-one patients were extubated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 26 publications
1
11
0
2
Order By: Relevance
“…These findings are consistent with the findings of Kawar et al [23], where they found that a Δtdi% >30% had a sensitivity of 95% and a specificity of 68% for extubation success. Similar results were also demonstrated by Farghaly and Hasan [24] and Alam et al [25], where tdi-end expiration out-performed RSBI.…”
Section: Discussionsupporting
confidence: 87%
“…These findings are consistent with the findings of Kawar et al [23], where they found that a Δtdi% >30% had a sensitivity of 95% and a specificity of 68% for extubation success. Similar results were also demonstrated by Farghaly and Hasan [24] and Alam et al [25], where tdi-end expiration out-performed RSBI.…”
Section: Discussionsupporting
confidence: 87%
“…The AUROC was 0.422, which was similar to other studies. [ 24 - 26 ] The lower the cut-off value, the higher the predictability in RSBI. It has the advantage of considering the balance between respiratory load and effort.…”
Section: Discussionmentioning
confidence: 99%
“…Alam et al [ 32 ] reported that successful extubation was significantly correlated with DE with an area under the curve (AUC) of 0.83 ( p < 0.001) and sensitivity 77.8% and specificity 84.6%. These results were consistent with several other studies that showed promising findings for using NIV-NAVA to facilitate extubation in preterm infants [ 10 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%